Tombamentos de templos religiosos em Laranjeiras/Sergipe - Passos, Lucas Santos (2015)
This dissertation analyzes the cultural heritage surveys regarding to religious temples from Laranjeiras (Sergipe/Brazil). Since its was institutionalized (1937), Brazilian cultural heritage politics is characterized by diverse social groups which use their symbolic power to select what should be officially considered cultural heritage, in a way to legitimate their cultural goods - specifically those related to religions. In Laranjeiras, the cultural goods surveys fit into that profile: among the nine cultural heritage surveys, four are historic catholic churches, while two of them are Afro-Brazilian religious temples, also known as terreiros . The critical issue of this dissertation is how those six specific cultural heritage surveys were carried out. Such surveys are analyzed according to two purposes: the first aim is to describe the cultural heritage surveys. The second purpose is to analyze the rules created and followed, as well as the social agents authorized to create and follow them, in a way to legitimate their social groups and symbolic capital. To do so, my theoretical framework is Pierre Bourdieu´s keyconcepts, such as field, capital and symbolic power (BOURDIEU, 2001; 2002; 2013), I conclude that historic catholic churches are still privileged in Brazilian cultural heritage politics field, specially because of the relations between State and Religion in Brazil, which reflects the hegemony of the Catholic Church. Thus, there is only one Afro-Brazilian temple officially protected, called Terreiro Filhos de Obá protected by the state of Sergipe. Its national survey is still pending in IPHAN bureaucratic machine since the 1990´s.